1999
DOI: 10.1523/jneurosci.19-02-00828.1999
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Resetting of the Mammalian Circadian Clock

Abstract: The suprachiasmatic nuclei (SCN) contain the principal circadian clock governing overt daily rhythms of physiology and behavior. The endogenous circadian cycle is entrained to the light/dark via direct glutamatergic retinal afferents to the SCN. To understand the molecular basis of entrainment, it is first necessary to define how rapidly the clock is reset by a light pulse. We used a two-pulse paradigm, in combination with cellular and behavioral analyses of SCN function, to explore the speed of resetting of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 52 publications
7
86
1
Order By: Relevance
“…MKC-242 has been shown to prolong the light-induced increases in both per1 and per2 mRNA (Takahashi et al, 2002), which normally decay within a few hours (Best et al, 1999;Khammanivong and Nelson, 2000). Since both per mRNA and Per protein levels are correlated with behavioral phase shifting (Best et al, 1999;Masubuchi et al, 2005), it is possible that the greater phase advance to light observed with MKC-242 and NAN-190 may be due to their extended elevation of per, and thus Per protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MKC-242 has been shown to prolong the light-induced increases in both per1 and per2 mRNA (Takahashi et al, 2002), which normally decay within a few hours (Best et al, 1999;Khammanivong and Nelson, 2000). Since both per mRNA and Per protein levels are correlated with behavioral phase shifting (Best et al, 1999;Masubuchi et al, 2005), it is possible that the greater phase advance to light observed with MKC-242 and NAN-190 may be due to their extended elevation of per, and thus Per protein.…”
Section: Discussionmentioning
confidence: 99%
“…MKC-242 has been shown to prolong the light-induced increases in both per1 and per2 mRNA (Takahashi et al, 2002), which normally decay within a few hours (Best et al, 1999;Khammanivong and Nelson, 2000). Since both per mRNA and Per protein levels are correlated with behavioral phase shifting (Best et al, 1999;Masubuchi et al, 2005), it is possible that the greater phase advance to light observed with MKC-242 and NAN-190 may be due to their extended elevation of per, and thus Per protein. Such might be accomplished by allowing enhanced Per production from the lightinduced per mRNA or by affecting the stability of Per protein (which is known to alter phaseshift magnitude) (Gallego et al, 2006;Jakubcakova et al, 2007;Lee et al, 2007;Masubuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Resetting of the SCN oscillators is thought to occur rapidly after a light pulse (Best et al, 1999;Watanabe et al, 2001), and significant effort has been devoted to identifying the phenotype of retinorecipient SCN cells. Estimates of the size and identity of this population of light-responsive cells range from 20 to 40% of SCN cells and vary depending on the assay used [electrophysiology (Sawaki, 1979;Meijer et al, 1986;Aggelopoulos and Meissl, 2000) or IEG expression (Earnest et al, 1993;Silver et al, 1996;Castel et al, 1997;Aioun et al, 1998)].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that melatonin levels displayed a clear phase-advance from the next cycle, although the rhythm of the locomotor activity takes a few more days to exhibit an explicit phase advance. When a phase shift of the clock will be complete after exposure to a light pulse is an important question, and a two-lightpulse paradigm study of locomotor activity strongly suggests that the phase-resetting of the mammalian pacemaker is complete within several hours (33). This has also been supported by a recent finding at the clock gene level showing that the application of N-methyl-D-aspartate, an in vitro counterpart of a light-pulse in behavior, into the SCN slice of transgenic mice carrying the mPer1 promoter driven luciferase gene, induced the phase-shift of the mPer1 transcription rhythm within 2-3 hr (7).…”
Section: Light Induces Immediate Phase Shifts Of Circadian Melatonin mentioning
confidence: 99%